2016
DOI: 10.1108/maj-10-2014-1117
|View full text |Cite
|
Sign up to set email alerts
|

Interactive visual analysis of anomalous accounts payable transactions in SAP enterprise systems

Abstract: Purpose – The purpose of this paper is to demonstrate the technical feasibility of implementing multi-view visualization methods to assist auditors in reviewing the integrity of high-volume accounting transactions. Modern enterprise resource planning (ERP) systems record several thousands of transactions daily. This makes it difficult to find a few instances of anomalous activities among legitimate transactions. Although continuous auditing and continuous monitoring systems perform substantial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…() use visual analytics to monitor financial stability. In the management accounting field, visual analytics identifies anomalous and potentially fraudulent accounts payable transactions (Singh and Best ).…”
Section: Research Directionsmentioning
confidence: 99%
“…() use visual analytics to monitor financial stability. In the management accounting field, visual analytics identifies anomalous and potentially fraudulent accounts payable transactions (Singh and Best ).…”
Section: Research Directionsmentioning
confidence: 99%
“…Audits are highly complex social processes, and subject to the conflict of divergence of interests between shareholders and owners, which might affect auditor performance and independence (Arya & Glover, ; Suddaby, Gendrom, & Lam, ). Singh and Best () demonstrated the technical feasibility of implementing multiview visualization methods to assist auditors in reviewing the integrity of high‐volume accounting transactions. In connection to these findings and our prior discussion of the principal‐agent dilemma and the underlying risk of moral hazard, we argue that an approach that helps to analyze, identify, and visualize data in a better way reduces information asymmetry by making the data more accessible to both the principal and agent.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…It has been demonstrated that the human brain can process more information at a faster rate when the information is presented graphically than when it is presented in text or tabular formats (Lurie and Mason, 2007). Graphic displays allow auditors, especially novice auditors, to quickly comprehend the data, detect certain relevant patterns and identify trends and relationships that would take much more effort to identify if presented in tables (Vessey and Galletta, 1991;Singh and Best, 2016). Thus, visualization can be used in every phase of an audit, including decisions to accept or continue an audit engagement, audit planning, risk assessment, responding to risk assessments and tests of controls or substantive testing (AICPA, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, visualization is being used by some auditors to generate insights, increase the accuracy of conclusions and improve the efficiency and effectiveness of the auditing process (Singh et al, 2013;AICPA, 2015;Brown-Liburd et al, 2015;Cao et al, 2015;Singh and Best, 2016) [1]. Data visualization can be used to both explore and explain data (Alawadhi, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation